Trump’s Pre-Inauguration Rhetoric: A Neo-Colonial Blueprint Through Critical Theory - K M Vishnu Namboodiri; Agney GK (tripleC: Communication, Capitalism & Critique)
This article critically examines Donald Trump’s pre-inauguration rhetoric through the lens of critical theory, uncovering its neo-colonial and capitalist underpinnings. Drawing from the theoretical contributions of Jürgen Habermas, Louis Althusser, Kwame Nkrumah, Immanuel Wallerstein, and Guy Debord, the analysis demonstrates how Trump’s economic and militaristic declarations perpetuate global capitalist dominance. His rhetoric exemplifies the colonization of the lifeworld, the operation of ideological state apparatuses, and the spectacle of power, all of which work together to reproduce and legitimize neo-colonial exploitation. The synthesis of these critical theories provides a comprehensive critique, highlighting the ideological and structural mechanisms that sustain global inequalities and calling for a praxis of resistance towards a more equitable global order.